Assessment of the seismic behaviour of Gondar church using a continuum damage model - Bruno Luís Silva (2008)
Stone masonry elements compose a large number of constructions not only in Portugal but in many other countries. The analysis of such this type of constructions is a complex task, mainly due to the large variability of the material properties. This analysis becomes particularly important when the structures are submitted to dynamic type loads, especially seismic loads. In this paper, an ancient Portuguese XII century church (Gondar church) located in the northern region of Portugal is analyzed using a numerical model in order to assess its structural behaviour and vulnerability when submitted to a seismic load. This analysis was performed using the finite elements program Cast3M (CEA, 1999) and considering non linear material characteristics for the masonry walls. The stone masonry behaviour was reproduced using a continuum isotropic non linear damage model originally created for concrete structures, while for the roof wooden structure a linear behaviour model was adopted. The church was tested considering a rigid foundation and submitted to its self-weight and a ground motion accelerogram matching the church site conditions. The results are presented and discussed in terms of the church deformation, damage pattern and stress state, indicating the most vulnerable zones. These types of studies highly contribute to the definition of more effective retrofitting and strengthening solutions.